Discovery of hydroxy pyrimidine Factor IXa inhibitors. Issue 15 (1st August 2020) - Jayne, Charles L.; Andreani, Teresa; Chan, Tin-Yau; Chelliah, Mariappan V.; Clasby, Martin C.; Dwyer, Michael; Eagen, Keith A.; Fried, Steve; Greenlee, William J.; Guo, Zhuyan; Hawes, Brian; Hruza, Alan; et al.
Graphical abstract: Abstract: The synthesis and structure activity relationship development of a pyrimidine series of heterocyclic Factor IXa inhibitors is described. Increased selectivity over Factor Xa inhibition was achieved through SAR expansion of the P1 element. Select compounds were evaluated in vivo to assess their plasma levels in rat.